2014
DOI: 10.37757/mr2014.v16.n1.6
|View full text |Cite
|
Sign up to set email alerts
|

Frailty, Dependency and Mortality Predictors in a Cohort of Cuban Older Adults, 2003–2011

Abstract: INTRODUCTION Population aging translates into more people with chronic non-communicable diseases, disability, frailty and dependency. The study of frailty-a clinical syndrome associated with an increased risk of falls, disability, hospitalization, institutionalization and death-is important to improve clinical practice and population health indicators.OBJECTIVES In a cohort of older adults in Havana and Matanzas provinces, Cuba, estimate prevalence of frailty and its risk factors; determine incidence of depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Our results are not comparable with those obtained in previous studies reported in the Introduction. Most of them have estimated life expectancy in small and very localized groups, as [ 17 ] do. Others are specifically focused on studying the life expectancy of the population in nursing homes, such as [ 18 , 19 ] or [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are not comparable with those obtained in previous studies reported in the Introduction. Most of them have estimated life expectancy in small and very localized groups, as [ 17 ] do. Others are specifically focused on studying the life expectancy of the population in nursing homes, such as [ 18 , 19 ] or [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were studies of mortality in small groups. [ 17 ] analyzed a small sample of 2813 people aged over 65 years old in the provinces of Havana and Matanzas in Cuba. The authors sought both to assess risk and to detect and identify factors that influence the onset of dependence and that could be used as predictors of mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The care and the management of dementia differs country-by-country, depending on epidemiological figures, the long-term care (LCT) system, welfare regimes, and level of country income. In Latin America, the prevalence of diagnosed dementia in 2010 was 3.10 million cases, compared to 9.95 million in Europe, and an increase of 393% is expected by 2050, compared to an 87% rise in Europe [ 36 ]. The increasing number of diagnosed PWD will contribute to growing inequalities in low- and middle-income countries, where 15% of dementia-related costs is covered by social care, compared to 40% in high-income countries [ 37 ].…”
Section: Introductionmentioning
confidence: 99%